Niosome as a Drug Delivery Carrier for Sorafenib: Preparation, Investigation of Physicochemical Properties, and In Vitro Effects on HepG2 Cell Line - Mohammad Amin Raeisi Estabragh; Behzad Behnam; Masoud Torkzadeh-Mahani; Abbas Pardakhty (Advanced Pharmaceutical Bulletin)
Purpose: Sorafenib is known as one of the oral anti-cancer drugs used in liver cancer. However, its lipophilic nature can lead to side effects, variable pharmacokinetics, and poor absorption. The use of novel drug delivery systems, such as niosomes, may help address these issues and improve the effectiveness of sorafenib. Methods: Different niosomal formulations of sorafenib were prepared. The morphology, size analysis, and physical stability were investigated. The encapsulation efficiency percent of the selected formulations was measured using the dialysis method, and the release of sorafenib was checked for four hours using the Franz diffusion cell. The cytotoxicity and in vitro effect on the HepG2 cell line was investigated using the MTT assay and flow cytometry. Results: The mean volume diameter of Span 60/Tween 60/cholesterol (45/45/10 mole%) niosomal formulation was 6 µm with minimal size changes and good stability over six months of storage. The encapsulation efficiency percent of this formulation was 66.40±1.11, and 61.43±1.42 percent of the drug was released within 4 hours. In vitro release followed Higuchi kinetics. Cytotoxicity tests showed an IC50 of 7.5 µg/mL for the niosomal formulation, compared to 15.96 µg/mL for the sorafenib solution. Conclusion: Niosomes containing Span 60/ Tween 60/ cholesterol (45/45/10 mole%) are promising for loading and sustained release of sorafenib. The use of niosome as a carrier can enhance the effectiveness of sorafenib on the HepG2 cell line. This niosomal formulation of sorafenib shows potential for future studies.